Out of breath - Donovan, Rebecca (Melbourne, Victoria Penguin Books, 2013)
Emma trusts no one and she can't let anyone in, not when she knows all they'll find is darkness. But some people won't take no for an answer and Emma must decide if the hidden truths and painful secrets are enough to let go of the possibility of love - forever.
Keywords: Young women -- Fiction; College students -- Fiction; Abused children -- Fiction